Effect of locally tailored clinical guidelines on intrapartum management of severe hypertensive disorders at Zanzibar's tertiary hospital (the PartoMa study). Issue 1 (26th October 2018) - Maaløe, Nanna; Andersen, Camilla B.; Housseine, Natasha; Meguid, Tarek; Bygbjerg, Ib C.; van Roosmalen, Jos
Abstract: Objective: To estimate the effect of locally tailored clinical guidelines on intrapartum care and perinatal outcomes among women with severe hypertensive disorders in pregnancy (sHDP). Methods: A pre–post study at Zanzibar's low‐resource Mnazi Mmoja Hospital was conducted. All labouring women with sHDP were included at baseline (October 2014 to January 2015) and at 9–12 months after implementation of the ongoing intervention (October 2015 to January 2016). Background characteristics, clinical practice, and delivery outcomes were assessed by criterion‐based case file reviews. Results: Overall, 188 of 2761 (6.8%) women had sHDP at baseline, and 196 of 2398 (8.2%) did so during the intervention months. The median time between last blood pressure recording and delivery decreased during the intervention compared with baseline ( P =0.015). Among women with severe hypertension, antihypertensive treatment increased during the intervention compared with baseline (relative risk [RR] 1.37, 95% confidence interval [CI] 1.14–1.66). Among the neonates delivered (birthweight ≥1000 g), stillbirths decreased (RR 0.56, 95% CI 0.35–0.90) and Apgar scores of seven or more increased during the intervention compared with baseline (RR 1.17, 95% CI 1.03–1.33). Conclusion: Although health system strengthening remains crucial, locally tailored clinical guidelines seemed to help work‐overloaded birth attendants at a low‐resource hospital to improve care for women with sHDP. ClinicalTrials.org: NCT02318420. Abstract : Among women with severe hypertensive disorders at Zanzibar's referral hospital, locally tailored intrapartum guidelines were associated with care improvements and 44% risk reduction of stillbirth.